(untitled) - Coronel, Carlos (Boston, 2019)
Provide a balanced approach to databases as the market-leading, emphasizes the knowledge and skills necessary for success and makes databases accessible without overwhelming students. Readers gain a solid foundation in database design and implementation as diagrams, illustrations, and tables clarify in-depth coverage of database design. Students learn how successful database implementation involves designing databases to fit within a larger strategic data environment. Revised coverage of SQL introduces more examples and simpler explanations that focus on areas most important for a database career -- making supplementary SQL materials unnecessary.
Keywords: Database design,Thiết kế cơ sở dữ liệu